Pulsed direct current magnetic energy harvesting by robotic spot-welding in smart automotive factory. (15th December 2022) - Kim, Dong Hyun; Lee, Bo-Yeon; Min, Seongwook; Joe, Daniel J.; An, Jaehun; Kim, Byung Woo; Park, Yong Hyun; Kang, Se Kyu; Hwang, Geon-Tae; Lee, Keon Jae
Abstract: A magneto-mechano-electric (MME) generator is considered as a promising candidate for power supplying to IoT sensors in a smart factory by harvesting noise magnetic field. However, most studies have carried out only with alternating current (AC) magnetic field from laboratory and home surroundings. Here, we demonstrate a pulsed direct current (DC) magnetic field-driven MME generator to harvest energy from spot-welding process in a manufacturing facility of Hyundai Motor Company. By one-spot-welding process, the MME generator generated a open-circuit peak voltage of 7.4 V as well as a peak power of 0.8 mW. The generated electricity was utilized to charge the 10 µF capacitor from 0 to 4.8 V with five times spot-welding, meaning a lot of electricity could be harvested by thousands of spot-welding during vehicle assembly process. Finally, we demonstrated self-powered IoT system by charging 3.3 mF capacitor using MME generator to power multifunctional IoT sensor. Graphical Abstract: ga1 Highlights: Fabrication of pulsed direct current (DC) driven magneto-mechano-electric (MME) generator operated by spot-welding process. Achieving output peak voltage of 7.4 V and peak power of 0.8 mW from the spot-welding MME harvesting. Demonstration of self-powered IoT sensor with charging a capacitor by the MME generator.